2020
DOI: 10.3390/nu12051296
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Eating Speed and Incidence of Gestational Diabetes Mellitus: the Japan Environment and Children’s Study

Abstract: There is little evidence linking eating speed to gestational diabetes mellitus (GDM) incidence. We therefore aimed to evaluate the prospective association of eating speed with GDM incidence. Overall, 97,454 pregnant women were recruited between January 2011 and March 2014. Singleton pregnant women who did not have GDM, heart disease, stroke, cancer, type 1 diabetes, and/or type 2 diabetes at the time of study enrollment were eligible. Each woman was asked about her eating speed at that time via a questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…With respect to eating speed, the current findings are in agreement with previous research reporting that eating quickly is positively associated with hypertriglyceridemia [ 15 ], overweight [ 12 ] or obesity [ 18 ], gestational diabetes [ 44 ], and glucose intolerance [ 14 ]. In a three-year follow study involving 1314 Japanese university students ( n = 638 women), Yamane et al [ 13 ] showed that eating quickly was significantly associated with an increased risk of being overweight.…”
Section: Discussionsupporting
confidence: 92%
“…With respect to eating speed, the current findings are in agreement with previous research reporting that eating quickly is positively associated with hypertriglyceridemia [ 15 ], overweight [ 12 ] or obesity [ 18 ], gestational diabetes [ 44 ], and glucose intolerance [ 14 ]. In a three-year follow study involving 1314 Japanese university students ( n = 638 women), Yamane et al [ 13 ] showed that eating quickly was significantly associated with an increased risk of being overweight.…”
Section: Discussionsupporting
confidence: 92%
“…However, its association with GDM has been inadequately researched. To our knowledge, only one recent study conducted in Japan [20] found that, compared with women reporting a slow eating speed, those who reported a very fast eating speed had an increased incidence of GDM. This study only paid attention to the eating speed, while other dimensions have not been explored.…”
Section: Introductionmentioning
confidence: 93%
“…Women who reported very fast eating speed, compared with those reporting slow eating speed, were associated with an increased incidence of GDM, which may be largely mediated by increased body fat. [122]…”
Section: Othersmentioning
confidence: 99%
“…[121] Women who reported very fast eating speed, compared with those reporting slow eating speed, were associated with an increased incidence of GDM, which may be largely mediated by increased body fat. [122] New cravings in the first trimester of pregnancy were associated with dietary intake. Craving salty foods may predict reduced risk of developing GDM, whereas craving sweet food does not appear to alter one's risk.…”
Section: Othersmentioning
confidence: 99%